Establishing value of time for the inter-island passenger transport of the Western Visayas region, Philippines - Roxas, Nicanor R. (Animo Repository, 2016)
Transportation infrastructure planning process requires cost–benefit analysis in the evaluation of project proposals. Value of time (VOT) facilitates the conversion of travel time savings, which is a significant proportion of benefits in monetary terms. In cases where VOT has not been established, planners resort to crude estimates that often results in erroneous or biased measurements of benefits. This is the case of the Western Visayas region in the Philippines where transportation studies are rare. Secondary cities and its peripheral regions have often been overlooked subjects of transportation studies. In this study, multinomial logit models using revealed preference data were estimated to facilitate the calculation of the VOT. The total cost, square of the total cost, and total time were identified as significant explanatory variables affecting mode choice. The square of the total cost term was introduced in the models in order to account for income effect. Results indicate that VOT estimates for the inter-island passenger transportation between Iloilo and Negros Occidental generally range from 78.15PHP to 179.15PHP (1.91USD to 4.37USD) depending on trip and traveller characteristics. © 2015, Springer Science+Business Media New York.